The inertia of Hermitian block matrices with zero main diagonal - Fonseca, C. M. da (2000)
Let n1,n2,n3 be nonnegative integers. We consider partitioned Hermitian matrices of the formwhere each Xij is ni×nj and we characterize the set of the inertiasin terms of rij, Rij and the block orders.